Kentomonas gen. n., a new genus of endosymbiont-containing trypanosomatids of Strigomonadinae subfam. n - Votýpka, Jan; Kostygov, Alexei Yu; Kraeva, Natalya; Grybchuk-Ieremenko, Anastasiia; Tesařová, Martina; Grybchuk, Danyil; Lukeš, Julius; Yurchenko, Vyacheslav (Protist, 2014)
Compared to their relatives, the diversity of endosymbiont-containing Trypanosomatidae remains under-investigated, with only two new species described in the past 25 years, bringing the total to six. The possible reasons for such a poor representation of this group are either their overall scarcity or susceptibility of their symbionts to antibiotics that are traditionally used for cultivation of flagellates. In this work we describe the isolation, cultivation, as well as morphological and molecular characterization of a novel endosymbiont-harboring trypanosomatid species, Kentomonas sorsogonicus sp. n. The newly erected genus Kentomonas gen. n. shares many common features with the genera Angomonas and Strigomonas, such as the presence of an extensive system of peripheral mitochondrial branches distorting the corset of subpellicular microtubules, large and loosely packed kinetoplast, and a rudimentary paraflagellar rod. Here we also propose to unite all endosymbiont-bearing trypanosomatids into the new subfamily Strigomonadinae subfam. n.
Keywords: symbióza; druhová specificita; Bayes Theorem; fylogeneze; RNA, Ribosomal, 18S; Cloning, Molecular; Sequence Analysis, DNA; Phylogeny; klonování DNA; sekvenční analýza DNA; Trypanosomatidae; DNA, Viral; Models, Genetic; bacterial endosymbionts; Species Specificity; RNA, Protozoan; Sarcophagidae; pravděpodobnostní funkce; DNA virů; Likelihood Functions; DNA, Bacterial; DNA bakterií; Trypanosomatina; Animals; zvířata; phylogeny.; modely genetické; Kentomonas; Bayesova věta; RNA protozoální; Symbiosis; RNA ribozomální 18S